Women s Land Rights Under Traditional Authorities in Namibia: A Case Study of Aawambo Women s Land Rights in the Omusati Region in Relation to the Communal Land Reform Act (Act No.05 of 2002) - Martin, Yamilla (African Studies, 2024)
This study examines the significance of the Communal Land Reform Act (Act No. 05 of 2002) and its impact on Aawambo women's land rights in Namibia's rural areas under the jurisdiction of traditional authorities. The study primarily argues that seemingly progressive legal frameworks such as the Communal Land Reform Act (No. 05 of 2002) are not enough to ensure rural women access to secure land rights. This argument was reached by examining a disjuncture between what the Namibian legislation stipulates pertaining to women's land rights in rural areas and the reality on the ground. Despite these challenges, the study also demonstrates how a number of the Aawambo women participants have accessed rights to land for the first time through the Communal Land Reform Act (No. 05 of 2002). The gap this study has identified is that the Act itself is flawed as there was very limited public consultation and participation from rural communities, specifically rural women (Girma, 2016:24, Werner, 2008:12, Werner, 2017:16). The overall findings of the study offer valuable insights that may benefit future research, policy reforms, or organisations that strive to promote gender equality in rural land tenure systems in Southern Africa. The study contributes to the ongoing gender-sensitive debates regarding gender dynamics, women's land rights and rural land tenure in Namibia.